Fractal Analysis of the Performance of Tertiary Teachers and the Academic Performance of Their Students (Asia Pacific Journal of Social and Behavioral Sciences, 2013)
This study investigated the performance of faculty in instruction, research, and extension and its ability to predict the performance of students. There were 73 regular faculty members from the College of Arts and Sciences of the Bukidnon State University whose performance were taken from their Performance Evaluation System (PES) rating during the first semester of school year 2013-2014. A total of 715 sample students from a population of 3,285 were proportionately extracted from each faculty's students using Slovin's formula. The academic performances of students were their grade point average in their respective subjects from their corresponding teachers during the semester. Ruggedness of the data on the performance of faculty in instruction accounts for 87% of the ruggedness of the data on the academic performance of their students. Likewise, 67% and 62% of the ruggedness of the data on the academic performance of students were accounted for by the ruggedness of the data of the performance of teachers in research and extension, respectively. It is concluded that differences of the performance of the faculty in instruction, research and extension impact on the differences of the academic performance of the students.
Keywords: Fractal analysis, fractal dimension, robust measure, performance of teachers, performance of students